ANALYTICAL ARTICLE ON SEMANTIC AND SOCIAL FACTORS IN THE FORMATION OF THE TERMINOLOGY OF UZBEK OFFICIAL WORKING PAPERS - Qodirov Ma’murxon Murodxon o‘g‘li (Web of Journals Publishing, 2024)
The article analyzes the terminology of Uzbek official business papers. The author studies the importance of terms in documents and business papers in the fields of linguistics, law and management. The article emphasizes that the documents are effective and understandable through the clear and direct use of terms. The development and problems of these terms in the Uzbek language are also covered.
Keywords: Official business paper; Linguistics; Law; Business papers; Terms; Documents.